2019
DOI: 10.1093/workar/waz006
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries of the Construct of Unemployment in the Preretirement Years: Exploring an Expanded Measurement of Lost-Work Opportunity

Abstract: There is uncertainty related to whether retirement negatively affects health—possibly due to complexity around retirement decisions. Lost-work opportunity through unemployment or forced retirement has been shown to negatively affect health. Lost-work opportunity can be captured in two measurement fields, either a reported experience of being forced into retirement or reported unemployment. However, 17% of individuals retiring due to the loss of work opportunity identified in qualitative interviewing (i.e., une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…These unprecedented times have enormous implications for individual work lives, labor-market policies and practices, and public safety nets. They may also challenge how we measure employment and unemployment opportunities and constraints ( Hyde & Dingermans, 2017 ; Voss, Snih, Li, Hung, Richards, 2020 ). Our findings on NILF-other suggests the need for thinking about and studying who at different ages and life stages are essentially a type of discouraged worker, dropping out of the workforce in the face of the COVID downturn and thus not captured in unemployment statistics.…”
Section: Discussionmentioning
confidence: 99%
“…These unprecedented times have enormous implications for individual work lives, labor-market policies and practices, and public safety nets. They may also challenge how we measure employment and unemployment opportunities and constraints ( Hyde & Dingermans, 2017 ; Voss, Snih, Li, Hung, Richards, 2020 ). Our findings on NILF-other suggests the need for thinking about and studying who at different ages and life stages are essentially a type of discouraged worker, dropping out of the workforce in the face of the COVID downturn and thus not captured in unemployment statistics.…”
Section: Discussionmentioning
confidence: 99%
“…We urge that researchers need to discover more individual and organizational strategies that can effectively combat ageism. Szinovacz and Davey (2005) found that nearly 30% of participants in their study reported forced retirement, and this experience was found to be detrimental to employees' health (Rhee et al, 2016;Voss et al, 2020), financial well-being (Heisig & Radl, 2017), and life satisfaction (Dingemans & Henkens, 2014). Involuntary retirement often results from personal or environmental constraints such as health conditions, care obligations, job displacement, or discriminative practices (Szinovacz & Davey, 2005).…”
Section: Accommodative Career Managementmentioning
confidence: 99%
“…National survey tools assessing health and retirement ask about forced retirement decisions but do not adequately capture when older workers are nudged out of the labor force. 16 Unraveling the potential health effects for this population begins with better measurement.…”
Section: Learning Outcomesmentioning
confidence: 99%
“…Mixed-methods comparisons of survey to interviews data found that 17% of individuals who marked retirement as voluntary revealed multiple elements of forced retirement timing in interviews (i.e., retirement prompted by unemployment, temporary layoffs, company buy-outs, workforce reductions, or forced relocations). 16,17 A deep dive into the Health and Retirement Study data on earlier than planned retirements found 27% of early retirements were still unexplained after adjusting for multiple factors like health change, family situations, and caregiving. 18 Measuring this phenomenon is difficult, particularly in cases where retirement is the best choice between bad options.…”
mentioning
confidence: 99%